2020
DOI: 10.1016/j.jtho.2020.01.016
|View full text |Cite
|
Sign up to set email alerts
|

New Approaches to SCLC Therapy: From the Laboratory to the Clinic

Abstract: The outcomes of patients with SCLC have not yet been substantially impacted by the revolution in precision oncology, primarily owing to a paucity of genetic alterations in actionable driver oncogenes. Nevertheless, systemic therapies that include immunotherapy are beginning to show promise in the clinic. Although, these results are encouraging, many patients do not respond to, or rapidly recur after, current regimens, necessitating alternative or complementary therapeutic strategies. In this review, we discuss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
136
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 133 publications
(136 citation statements)
references
References 153 publications
(231 reference statements)
0
136
0
Order By: Relevance
“…SCLC represents 13% of lung cancer cases, with a 5-year survival rate of only 5%. Due to the aggressive nature of the disease, together with its acquired resistance to chemotherapy, the standard care for advanced SCLC has essentially remained stagnant for more than 30 years, until only very recently with the introduction of immunotherapy (Poirier et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…SCLC represents 13% of lung cancer cases, with a 5-year survival rate of only 5%. Due to the aggressive nature of the disease, together with its acquired resistance to chemotherapy, the standard care for advanced SCLC has essentially remained stagnant for more than 30 years, until only very recently with the introduction of immunotherapy (Poirier et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Although systemic therapies including immunotherapy have begun to show promising outcomes in the past few years, the outcomes of SCLC patients remain to be substantially impacted [ 24 ]. Chemotherapy and radiation therapy are still the main stay approaches regardless of the stage of LD or ED [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…Sloman et al ( 12 ) investigated the role of several immunohistochemical markers, including synaptophysin and CD 44 in a small sample of 28 patients, and could not find a significant correlation concerning survival, whereas in an analysis by Drivsholm et al ( 47 ), the expression of chromogranin A in plasma correlated with a worse OS and the stage of disease. Recent studies have shown that SCLC has four different molecular subtypes with a different neuroendocrine character each identified by their key transcriptional regulator ( 3 , 48 ). A subset of small cell lung carcinomas shows loss of the typical neuroendocrine markers.…”
Section: Discussionmentioning
confidence: 99%
“…SCLC is an aggressive, high-grade neuroendocrine tumor associated with a short doubling time, a high growth fraction, and early development of widespread metastases, which contribute to the extremely poor prognosis of the disease ( 1 3 ). In an era of precision medicine, there is an increasing need for defining biomarkers that could assist in therapeutic decision making.…”
Section: Introductionmentioning
confidence: 99%